Horseshoe Crab Aquaculture as a Sustainable Endotoxin Testing Source - Tinker-Kulberg, Rachel; Dellinger, Kristen; Brady, Terry E.; Robertson, Lee; Levy, Jerrold H.; Abood, Sarah K.; LaDuca, Frank M.; Kepley, Christopher L.; Dellinger, Anthony L. (Frontiers in Marine Science, 2020)
Horseshoe crab (HSC) hemolymph is the source of Limulus amebocyte lysate (LAL), a critical component in sterility testing that ensures drug and medical device safety for millions of patients every year. Wild HSC populations have been declining as a result of use as whelk and eel bait, and largely due to capture and bleeding for hemolymph, primarily while spawning, thus posing significant biomedical supply and species viability risks. We investigated aquaculture as an alternative to current practices as a means to foster conservation by establishing a sustainable endotoxin testing resource. We found HSC aquaculture to be practicable based on routine hemolymph harvesting, batch uniformity, and LAL quality, while safeguarding animal wellbeing. Achieving sustainable LAL production could satisfy industry needs for several years with a fraction of one year’s current capture with low-impact, year-round harvesting of a finite cohort. Sustainable supplies of LAL could also be adapted to address daunting trends in septicemia and antimicrobial resistance. LAL is uniquely sensitive and specific for gram-negative bacteria, which represent 70-80% of pathogens typically attributed to sepsis. Early diagnosis of bacterial infection and timely antibiotic therapy can reduce patient mortality. However, erratic results associated with interfering substances plagued efforts to adapt LAL for clinical use in the past. Our efforts to develop new methods have yielded a promising LAL screening technique to detect a gram-negative bacteria and endotoxins in human blood.